2015
DOI: 10.1088/0029-5515/55/11/113021
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of electrostatic turbulence induced transport in presence of resonant magnetic perturbations in RFX-mod

Abstract: Three-dimensional non-axisymmetric magnetic fields are purposely applied to toroidally symmetric fusion plasmas in order to modify transport of heat and particle fluxes to the plasma-facing components (PFCs), and specifically to control and suppress Edge Localized Modes (ELMs) in H-mode tokamak plasmas. This paper presents a comparative study between two magnetic configurations available in the RFX-mod device, namely the original reversed-field pinch configuration and the more recent low-field circular ohmic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In particular, the studies of the effects of the RMPs on turbulence and transport are in progress. The experiments have clearly shown the increase of turbulence and of the transport in the presence of RMPs in tokamak plasmas [4]- [7] and in other configurations as RFX [8] and LHD [9]. Theoretical models and numerical simulations have confirmed these effects ([10]- [12] and the references there in)…”
Section: Introductionmentioning
confidence: 66%
“…In particular, the studies of the effects of the RMPs on turbulence and transport are in progress. The experiments have clearly shown the increase of turbulence and of the transport in the presence of RMPs in tokamak plasmas [4]- [7] and in other configurations as RFX [8] and LHD [9]. Theoretical models and numerical simulations have confirmed these effects ([10]- [12] and the references there in)…”
Section: Introductionmentioning
confidence: 66%
“…Reduction of turbulent fluctuation by loss of the pressure gradient inside the flat magnetic island has been observed in [17,18]. Experimental measurements of the poloidal flow in the vicinity of the magnetic island have been reported in [19,20,21,22,23], and they found that the flow shear across the island can be important in multiscale interactions and consequently in the transport across the island. Recent simulation studies have predicted multiscale interactions via both pressure and flow profiles.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, due to finite Larmor effects [12,13], the E ×B diffusion coefficients decay algebraically at large energies. In fusion devices such as ASDEX Upgrade [14,15], DIII-D [16,17] and others [18,19] it has been found experimentally that the interaction of fast particles with RMPs leads to a substantial increase in radial transport and, consequently, fast ion loses.…”
Section: Introductionmentioning
confidence: 99%